MULTI-LEVEL MONITORING OF THE DEVELOPMENT OF PRESCHOOL CHILDREN IN EDUCATIONAL LOCATIONS USING THE “2 ON 2” MODEL AS THE BASIS OF STRATEGIES FOR SUPPORTING MENTAL HEALTH AND OVERCOMING EDUCATIONAL LOSS - Косенчук, Ольга; Тарнавська, Наталія (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2025)
The article presents the results of a multilevel monitoring of preschool children’s development under conditions of short-term attendance at educational locations based on the “2 on 2” model, implemented in Ukraine during the period from September 2024 to February 2025 (second wave). It is shown that the short-term organization of the educational process makes it possible to identify learning losses and gaps, plan psychological and pedagogical support, intensify the educational process, and increase its effectiveness. The structure of the multilevel monitoring is outlined, encompassing three interrelated levels: (1) monitoring the child’s development across key domains and indicators; (2) organizational and methodological support aimed at the development of programmatic and methodological resources, professional growth, and psychological support for project participants; and (3) assessment and strengthening of the resources of the educational environment, taking into account the specifics of the “2 on 2” model. The research design, sample, and methods of data collection, aggregation, and interpretation are described. Statistical results of the baseline monitoring are presented, indicating the presence of systemic learning losses and gaps. A comprehensive model for supporting and maintaining children’s mental health and overcoming learning losses is introduced, integrating psychological-pedagogical, organizational, and environmental strategies. It is demonstrated that the implementation of this model contributed to positive developmental dynamics in children, as confirmed by the results of the final monitoring, and attests to its effectiveness under conditions of wartime crisis.